2018
DOI: 10.1007/s40615-018-0464-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Trends in Racial Disparities for Peri-Operative Outcomes with the New Kidney Allocation System (KAS) Implementation

Abstract: KAS had substantial impact on transplant rates by race/ethnicity. KAS also led to increased costs, readmissions, and delayed graft function (DGF) across all racial/ethnic groups. The impact of KAS on ICU cases solely within Hispanics requires further investigation into potential etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…However, studies from high volume centers demonstrated that within minorities, specifically African Americans and Hispanics, rates of transplantation had increased after KAS. 6 , 12 Our institution did have the same results. Even though our kidney transplant list is composed of mostly, if not all, Hispanics.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, studies from high volume centers demonstrated that within minorities, specifically African Americans and Hispanics, rates of transplantation had increased after KAS. 6 , 12 Our institution did have the same results. Even though our kidney transplant list is composed of mostly, if not all, Hispanics.…”
Section: Discussionsupporting
confidence: 65%
“…According to a short-term study from Sanchez et al, the implementation of the new KAS has resulted in a more equitable distribution of kidney transplants; there was a decrease in transplants for Caucasians and an increase for Hispanics and African Americans. 6 Other studies suggest the new system has resulted in a higher proportion of transplants in patients with high cPRA with higher quality grafts. 7…”
Section: Introductionmentioning
confidence: 99%
“…Recent changes in deceased donor allocation in the United States (US) under the new Kidney Allocation System (KAS) implemented in 2014 were associated with an increase in DGF—presumably due to increased cold ischemia time that resulted from increased organ sharing and increased dialysis vintage among recipients 11,12 . With the increased focus on the use of less‐than‐ideal organs to lower the currently high discard rate, there is concern of a further increase in the incidence of DGF in the United States—and the attendant costs associated with this complication 12,13 . Increased costs that are incurred when using less‐than‐ideal organs that progress to DGF potentially deter transplant centers from accepting these organs despite evidence that this approach would still be cost‐effective for the healthcare system vs staying on dialysis, while also providing significant quality of life and mortality benefits 13 .…”
Section: Introductionmentioning
confidence: 99%
“…With the increased focus on the use of less‐than‐ideal organs to lower the currently high discard rate, there is concern of a further increase in the incidence of DGF in the United States—and the attendant costs associated with this complication 12,13 . Increased costs that are incurred when using less‐than‐ideal organs that progress to DGF potentially deter transplant centers from accepting these organs despite evidence that this approach would still be cost‐effective for the healthcare system vs staying on dialysis, while also providing significant quality of life and mortality benefits 13 . We attempt, using direct hospital‐reported charge data from the Premier Healthcare Database, to estimate the increased financial costs incurred with DGF following kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the OPTN data up to 2016 found a 69% higher odds in delayed graft function in recipients <10 years of age post-KAS compared with pre-KAS explained by age or size of donors and pretransplant dialysis duration (11). Separately, another study reported higher likelihood of delayed graft function post-KAS for all adults but more so for those of Black or Hispanic race and ethnicity (6). Our study finds that with prolonged follow-up time, delayed graft function did not differ among racial and ethnic pediatric groups.…”
Section: Discussionmentioning
confidence: 99%